Presentation: Antiquity and Actuality of Irrigation in the Andes (II) - Iguiñiz Echeverría, Javier (1986)
In the first of the two volumes of Allpanchis devoted to irrigation, Jeanette Sherbondy was kind enough to write the introduction and incorporate her experience on the subject by synthesizing the arguments of the articles. This presentation note may not repeat the versation and sharpness of the previous one. In this volume 2, the articles analyze the problem of irrigation from various perspectives. Perhaps the main one is the one that studies the relationship between, on the one hand, the State and/or development agencies, and, on the other, the community.